REFLEKSI IT: Upaya Edukasi Kepada Masyarakat Guna Menumbuhkan Bibit yang Melek Teknologi - Ima Frafika Sari; Andriani (Abdimas Indonesian Journal, 2022)
This research used a qualitative descriptive method with the ABCD (Asset, Based, Community Development) system. The problems present during society will provide lessons and the discovery of new technological things. In the current digital era, people are strongly encouraged to be technology literate. The people of Gasang Village are not very familiar with technology; thus technological development can still be lacking. The purpose of this service research is to provide awareness to the public about technological developments. Education is given, ranging from hardware to social media that is currently circulating. This approach is carried out in stages, starting from computer training, Microsoft word, social media to other accounts. This training uses a one day one theme system. Thus, people can focus on one theme inone day. The results of this study are changes that occur significantly to people who are not familiar with computers atfirst can now apply them. People who initially did not know social media now know it as a technology, using it as a medium of information and marketing. The positive side of this research is the public interest in developing following thetimes.